If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 + 2x + x = 180 Combine like terms: 2x + x = 3x 90 + 3x = 180 Solving 90 + 3x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 3x = 180 + -90 Combine like terms: 90 + -90 = 0 0 + 3x = 180 + -90 3x = 180 + -90 Combine like terms: 180 + -90 = 90 3x = 90 Divide each side by '3'. x = 30 Simplifying x = 30
| 3(2f+4)=8+2v+v | | 1.2-x=0.2 | | 3y-6a= | | 0.37(28+62.7)=56.758 | | 4y+2=3y+5 | | 12y=1+2 | | x+7=3(4+x)-7x | | 3x-1y=163 | | -2y=12+x | | -a(a-1)=0 | | 10x-5=3y | | X+20x=180 | | 73=4n-7 | | 4(d-3)=-8 | | 2(6+s)+s-10+s=100 | | 2.5x(x+2)+4.5x=1.5(x-4) | | 3x+x-3=25 | | 0.2(n-5)=0.3n+6-4+0.1n | | -.55(x+2)=4.4 | | -8=(3-d)4 | | -2x+4y=-40 | | 1600=p(1+0.06) | | 5m-15-20m+5= | | (3x+6)(2x-12)(x+8)=0 | | -4y-2x=-8 | | -1.5x+y=320 | | 6f-13=24f-11 | | 6f-13=24f | | 1.4x+2y=800 | | 5*x-9+2*x+3=90 | | -4(x-2)+6x-15-x(4-3)=14-3(x+2)+7x-4 | | 0=-16 |